Perceived Symptoms in People Living with Impaired Glucose Tolerance. (12th July 2011) - Andersson, Susanne; Ekman, Inger; Lindblad, Ulf; Friberg, Febe
Abstract : The aim of the study was to identify symptoms in people with impaired glucose tolerance (IGT) and describe their experiences of living with the symptoms which they related to their condition. Twenty-one participants, from a cross-sectional population-based study, diagnosed as having IGT, were invited for an interview. The interviews were analyzed in two phases by means of a manifest and latent content analysis. The narratives included seven categories of symptoms (and more than 25 different symptoms) presented by the respondents. This study shows that symptoms such as the patient's own interpretation of different perceptions in the body must be considered, as well as signs and/or objective observations. Symptoms ought to be seen as complementary components in the health encounter and health conversation. The results of this study indicate that health professionals should increase their awareness of the balance between the implicit and the explicit bodily sensations that individuals communicate. Further studies are needed.